Literature review on the consequences of enterprise digital transformation based on CiteSpace: Hotspots, trends and opportunities - Juan, Wang; Kharuddin, Khairul Ayuni Mohd; Ismail, Rina Fadhilah (Edelweiss Applied Science and Technology, 2025)
The booming of the digital economy has sped up the development of several industries. Through digital transformation, companies are continuously enhancing their capacity to adjust to the external economic environment, which affects every facet of their business. However, there is a scarcity of comprehensive analysis of research on the hotspots, trends and opportunities on the consequences of Enterprise Digital Transformation (EDT). Therefore, this study uses CiteSpace to visually analyze a knowledge network based on a sample of 817 publications from 2018 to 2024. The results indicate that since 2021, the count of published papers in this area has drastically increased. The keyword analysis shows that EDT, performance, innovation, environmental, social and governance (ESG), and big data have become the hotspots in this research area. Future researchers mainly focus on the impact of EDT on firm financial performance, sustainable development, and environmental performance. The research methods used were primarily questionnaire survey and secondary data. majority of the present research focuses on how management, innovation, and finances are affected by EDT. The findings of this study are beneficial for researchers to find ideas and references for future studies on the consequences of EDT.